Morpho-molecular characterization of two Pleosporales species, Montagnula thevetiae and Thyridaria thailandica sp. nov. in northern Thailand - Tun, Zaw Lin; Bhunjun, Chitrabhanu S.; Maharachchikumbura, Sajeewa S. N.; Alotibi, Fatimah; Hyde, Kevin D. (Phytotaxa, 2024)
In this study, a new record of Montagnula, and a new species in Thyridaria are introduced based on morphological characteristics and multi-phylogenetic analyses of SSU, LSU, ITS, tef-1α, and rpb2 sequences. These isolates were obtained from dead woody litter in northern Thailand. The newly isolated Montagnula thevetiae (Didymosphaeriaceae) shares similar characteristics to other Montagnula species by having immersed, globose, reddish-brown to brown ascomata with papillate ostioles. Additionally, multi-gene phylogenetic analysis placement of M. thevetiae within the genus Montagnula. The novel species, Thyridaria thailandica (Thyridariaceae) shares similar characteristics to other Thyridaria taxa by having globose to subglobose and ostiolate ascomata and it is phylogenetically closely related to T. aureobrunnea. However, T. thailandica has larger ascomata and asci compared to T. aureobrunnea. This study provides updated information on the taxonomy of Montagnula and Thyridaria taxa, based on morphology and phylogenetic evidence.